Estimated investment cost for the implementation of good practices in livestock farms to choose a sustainable certification: case study of the region Esparza, Costa Rica - Castro Vargas, Rodrigo E. (2011)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 2011